2008
DOI: 10.3122/jabfm.2008.06.080103
|View full text |Cite
|
Sign up to set email alerts
|

Angioedema After Local Trauma in a Patient on Angiotensin-Converting Enzyme Inhibitor Therapy

Abstract: Angioedema is a side effect that is often associated with the use of angiotensin-converting enzyme (ACE) inhibitor medications. These medications result in increased levels of circulating bradykinins. This case illustrates the result of a local traumatic event to the upper lip, presumably causing marked bradykinin release in a patient who was taking an ACE inhibitor. The local release of bradykinin from trauma, in addition to decreased bradykinin catabolism secondary to ACE inhibitor therapy, resulted in angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The available literature contains many case reports of angioedema in surgical patients, suggesting direct injury caused by perioperative trauma (eg, intubation, lumbosacral spine surgery, c-spine surgery, shoulder surgery) as a trigger for angioedema in patients taking ACEIs or angiotensin II receptor blockers [ 3 , 7 , 14 , 15 ]. However, our search in PubMed (March 10, 2023) yielded only 1 case of local trauma-related angioedema outside the perioperative period, in a patient who bit her upper lip [ 8 ]. The patient was on an ACEI; no such event is reported with ARBs in a nonsurgical setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available literature contains many case reports of angioedema in surgical patients, suggesting direct injury caused by perioperative trauma (eg, intubation, lumbosacral spine surgery, c-spine surgery, shoulder surgery) as a trigger for angioedema in patients taking ACEIs or angiotensin II receptor blockers [ 3 , 7 , 14 , 15 ]. However, our search in PubMed (March 10, 2023) yielded only 1 case of local trauma-related angioedema outside the perioperative period, in a patient who bit her upper lip [ 8 ]. The patient was on an ACEI; no such event is reported with ARBs in a nonsurgical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many cases of spontaneous angioedema and perioperative angioedema in patients taking ACEIs have been reported [ 7 ]. However, angioedema following local trauma in patients taking ARBs is rare in the literature, and our literature review in PubMed revealed only 1 similar case [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many non-genetic factors are associated with ACEi-A. This ADR is more prevalent in women, elderly, smokers, people with history of drug rash, chronic heart failure, coronary artery disease and seasonal allergy, local trauma, as well as patients undergoing transplantation and under immunosuppressive conditions, 14,129,130 whereas it is reported to be lower in patients with type-2 diabetes. 14 The interaction of genetic and non-genetic factors has no doubt complicated the finding of any strong genetic associations and also suggests the possibility of epigenetic dysregulation as a contributor.…”
Section: Discussionmentioning
confidence: 99%
“…This ADR is more prevalent in women, elderly, smokers, people with history of drug rash, chronic heart failure, coronary artery disease and seasonal allergy, local trauma, as well as patients undergoing transplantation and under immunosuppressive conditions, 14,129,130 whereas it is reported to be lower in patients with type-2 diabetes. This ADR is more prevalent in women, elderly, smokers, people with history of drug rash, chronic heart failure, coronary artery disease and seasonal allergy, local trauma, as well as patients undergoing transplantation and under immunosuppressive conditions, 14,129,130 whereas it is reported to be lower in patients with type-2 diabetes.…”
Section: Genes In Fibrinolytic and Coagulation Pathwaysmentioning
confidence: 99%
“…ACE inhibitor-induced angioedema after cervical surgery is a rare condition. A few cases of angioedema following local trauma in patients using ACE inhibitors have been published [37]. We present an interesting case of severe angioedema causing airway obstruction after anterior cervical surgery in a patient using ACE inhibitors.…”
Section: Introductionmentioning
confidence: 99%